Theoretical and Methodological foundations for Creating a Historical Exhibition in the Museums of Kazakhstan - Ibrayeva, Akmaral; Sydykov, Aybek (Turkic Studies Journal, 2024)
This article addresses significant issues in museum work, a key aspect of implementing Kazakhstan’s cultural policy. The study and promotion of history in museums are conducted through expositions and exhibitions. One of the primary tasks of modern museums is to emphasize the importance of tangible culture in the era of digital communication as a crucial resource for national competitiveness and global recognition. As cultural institutions implementing state strategic policies, museums present Kazakhstan’s historical and cultural values to the world through National Exhibitions of the country in particular, and of Turkic culture in general. This academic article discusses the conceptual framework for creating a historical exhibition covering periods from ancient times to the Kazakh Khanate, using unique exhibits from the National Museum’s collection. The methodology for creating a world-class national exhibition is based on civilizational principles. The authors aim to to present a comprehensive image of Kazakh history through museum exhibitions, reflecting the cultural code of the steppe civilization. The authors view museums as cultural, educational, scientific institutions that play a crucial role in popularizing and preserving national values. They provide scientifically grounded concepts for national exhibitions by addressing theoretical and methodological issues and methods of exhibition creation.